Cuidado em território de exclusão social: covid-19 expõe marcas coloniais - Camilo, Claudia; Kahhale, Edna; Ferreira, Maria Luísa; Schveitzer, Mariana (Saúde e Sociedade, 2021)
A intersecção de gênero, raça e classe marca os territórios de exclusão social, especialmente em um país que carrega cicatrizes da colonialidade patriarcal e capitalista em suas estruturas, como é o caso do Brasil. O objetivo deste trabalho é compreender o cuidado em um desses territórios: a cidade de Cubatão/SP. A investigação, feita entre 2017 e 2020, incluiu a pandemia da covid-19, que sobrecarregou o cuidado no território. O método foi a pesquisa qualitativa, com oficinas, observação participante e entrevistas de profundidade. O cuidado era majoritariamente oferecido por mulheres, líderes comunitárias e profissionais da atenção primária do Sistema Único de Saúde. Para analisar os dados, utilizou-se a hermenêutica de profundidade. O referencial teórico foi a costura das teorias feministas da ética do cuidado, ecofeministas e interseccionais. A pesquisa revelou diversos desafios e potencialidades, como o cuidado ético-político, eixo da busca por justiça socioambiental. , Abstract The intersection of gender, race and class marks the territories of social exclusion, especially in a country that carries scars of a patriarchal and capitalist colonialism in its structures, as is the case in Brazil. The objective was to understand care in this territory of exclusion in Cubatão, São Paulo, Brazil. The research, conducted between 2017 and 2020, included the pandemic of COVID-19, which overloaded care in this territory. The method was qualitative research, with workshops, participant observation and in-depth interviews. The care delivered by community leaders and primary health care professionals from the Brazilian National Health System was mostly performed by women. For data analysis, depth hermeneutics was used. The theoretical reference was the perspective of feminists: ecofeminist, intersectional and Care Ethics. The study showed several challenges and the ethical-political care as an axis in the search for social and environmental justice.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; brésil; care; covid-19; intersectionnalité; pandémie; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; travail; écoféminisme

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Informal caregiving and strains: Exploring the impacts of gender, race, and income - Willert, Bria; Minnotte, Krysta Lynn (Applied Research in Quality of Life, 2021)
Informal caregivers are those who provide care for others without compensation. In the US, 85 % of elderly individuals receive care from an informal caregiver, and this number is expected to increase. Caregivers often experience different types of strain, stemming from physical, emotional, and financial demands. Guided by intersectionality theory, this study explores the relationships between informal caregiving strains and gender, race, and income, along with various control variables, including age, marital status, education, number of hours spent providing care, and employment status. Data from the 2015 Caregiving in the US survey (N = 1248) were used. Findings indicated male informal caregivers reported more financial strain compared to females. White women reported more emotional strain than women of color, and those with higher incomes reported less financial strain. Gender, race, and income were not significantly related to physical strain among informal caregivers. Implications, limitations, and suggestions for future research are discussed. © 2019, The International Society for Quality-of-Life Studies (ISQOLS) and Springer Nature B.V.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; care; détresse psychologique; intersectionnalité; proche aidance; projet charge mentale; périodes historiques; régions géographiques; soins aux; stress financier; thématiques; états-unis

Là où je me terre: roman - Dawson, Caroline (Les éditions du remue-ménage, 2020)
« Valparaíso, décembre 1986, tremblement de terre entre les quatre murs d'une maison. Un homme et une femme annoncent à leurs enfants qu'il faut tout laisser derrière et fuir le Chili de Pinochet. C'est Noël, la petite Caroline a sept ans et elle aura la nausée durant tout le voyage. La fillette atterrit à Montréal. En plus de la neige dehors, il y a le tapis rouge vin de l'hôtel Ramada qui accueille les personnes réfugiées en attente de papiers. Il y a aussi Passe-Partout qui semble s'adresser à elle à travers le téléviseur. Après le premier appartement à Montréal-Nord, la classe d'accueil de madame Thérèse qui lui apprend le français, les enfants qui se moquent de ses cheveux et de sa boîte à lunch, la misère des rues d'Hochelaga, il y aura tout ce temps passé dans les banques où ses parents font des ménages. Entre l'exil, les fantômes du passé et le jeu des différences, la petite Caroline camouflera sa furieuse envie de vivre pour ne plus détonner et devenir une immigrante modèle. Mais comment apprend-on à ne plus s'effacer? Peut-on embrasser une nouvelle culture sans renier ses origines? Lumineux et vivant, Là où je me terre sonde la possibilité d'aimer et de lutter sans ne plus avoir à fuir. »
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; intersectionnalité; inégalités; justice sociale; lit301N; littérature; maternité; montréal; premier cycle; périodes historiques; québec; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; écriture des femmes*

Kiffe ta race - Binge Audio - Ly, Grace; Diallo, Rokhaya (Kiffe ta race - Binge Audio, 2018)
Pourquoi le mot « race » est-il tabou ? Qu’en est-il quand on est, à la fois, victime de discriminations raciales et sexuelles ? Comment assumer son identité plurielle ? Un mardi sur deux, Rokhaya Diallo et Grace Ly reçoivent un·e invité·e pour explorer les questions raciales sur le mode de la conversation et du vécu.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; care; com5170; communication; corps; cours; discipline; europe; france; identités; intersectionnalité; journalisme; justice sociale; militance; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; violences

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Boundaried caring and gendered emotion management in hospice work - Cain, Cindy L. (Gender, Work and Organization, 2017)
Caring work, which is premised on caring for and caring about recipients, involves a great deal of emotion management. Feeling rules shape expectations about emotion management and are informally shared through workers’ narratives about quality work. Using qualitative data from hospice workers in the southwestern US, I find that narratives of quality within hospice include emotion-management skills such as listening, truly caring, keeping calm and maintaining boundaries. Through an analysis of how workers discuss and map skills onto individual women and men co-workers, this article highlights two gendered patterns. First, even when women and men are thought to share high-quality skills, the ways these skills are described reinforce naturalistic understandings of gender. Second, men are seen to hold a broad range of emotion-management skills, but women are not described as holding the most important emotion-management skill: keeping boundaries. Understanding this differential application of emotion-management skills helps us to understand how gender and gender inequality are reproduced within caring work. © 2017 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; intersectionnalité; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; soins palliatifs; systèmes d'oppressions; thématiques; travail; travail du care; travailleureuses de la santé; émotions; états-unis

The mask you live in - Newsom, Jennifer Siebel; Anthony, Jessica; Kanopy (Firme) (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Évaluation des besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale - Larochelle, Émilie (2010)
Les femmes handicapées constituent un groupe de la population particulièrement vulnérable à la violence conjugale. En effet, elles risqueraient davantage que les autres femmes d’être victimes de violence de la part de leur conjoint et subiraient des formes plus sévères de violence (Brownridge 2006). Elles rapporteraient également de plus longues périodes d’abus (Nosek et autres 2001a). Pourtant, peu de ressources spécialisées en matière de violence conjugale leur sont accessibles, et les études sur l’accessibilité de ces ressources ainsi que sur la violence conjugale à l’égard des femmes handicapées se font rares. C’est dans ce contexte que l’Office des personnes handicapées du Québec (l’Office) et le ministère de la Santé et des Services sociaux (MSSS) se sont engagés à documenter la problématique de la violence conjugale envers les femmes handicapées dans le cadre du Plan d’action gouvernemental 2004-2009 en matière de violence conjugale (Québec 2004). Afin de remplir cet engagement, l’Office, en partenariat avec le MSSS, a entrepris en avril 2008 le projet intitulé Évaluation des besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale. Ce projet vise à : 1. Documenter la problématique de la violence conjugale envers les femmes handicapées. 2. Évaluer les besoins d’adaptation des services offerts aux femmes handicapées victimes de violence conjugale par le réseau de la santé et des services sociaux et les maisons d’hébergement. 3. Formuler des recommandations visant la prévention de la violence conjugale auprès des femmes handicapées ainsi que l’adaptation des services aux réalités particulières vécues par celles-ci. Ce projet d’évaluation, par ses résultats et ses recommandations, contribue également à répondre à l’une des priorités d’intervention de la politique gouvernementale À part entière : pour un véritable exercice du droit à l’égalité, soit agir contre toute forme d’exploitation, de violence et de maltraitance (Québec 2009 : 31). Rappelons que cette politique a été adoptée le 4 juin 2009 par le gouvernement du Québec et a pour but d’accroître, sur une période de dix ans, la participation sociale des personnes handicapées.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; amériques; approches et analyses; canada; care; cours; discipline; intersectionnalité; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; thématiques; travail social